STRATEGI GRAPHIC ORGANIZER WHAT HAPPENED DAN MOTIVASI BELAJAR TERHADAP KETERAMPILAN MENULIS NARASI PESERTA DIDIK KELAS V GUGUS I KECAMATAN PADANG UTARA - Triyana Yetra (Jurnal Inovasi Sekolah Dasar, 2020)
Abstract               This study aims to test the influence of strategic Graphic Organizer What Happened and motivation to writing narrative skills grade V students claster I North Padang district. Used quasy experiments with design factorial design  2 x 2. Experimental group and control recruited cluster random sampling. Subject totaling 61 people class V year 2016/2017. Test performance used to measure the writing skills narrative learners and questionnaire is used to measure the motivation students. data were analyzed with test t-test and analysis of variance two-way. The results showed that there were significant differences in learning outcomes between students with high and low motivation who used graphic organized strategy what happened with students who were taught using conventional strategies, There was no significant interaction between graphic organized strategy what happened and motivation for narrative writing skills student. No significant interaction between the strategy Graphic Organizer What Happened and motivation to writing skills narrative students. Keywords: Strategic Graphic Organizer What Happened, motivation, writting narative Abstrak               Penelitian ini bertujuan untuk menguji pengaruh Strategis Graphic Organizer what Happened dan motivasi terhadap keterampilan menulis narasi siswa kelas V gugus I Kabupaten Padang Utara. Jenis penelitian yang digunakan adalah quasy eksperimen dengan desain faktorial desain 2 x 2. Pngambilan kelas eksperimen dan kontrol menggunakan tekni Cluster Random Sampling. Subjek berjumlah 61 orang kelas V tahun 2016/2017. Tes unjuk kerja digunakan untuk mengukur kemampuan menulis narasi peserta didik dan angket digunakan untuk mengukur motivasi peserta didik. Data dianalisis dengan uji t-test dan analisis varian dua arah. Hasil penelitian menunjukkan bahwa terdapat perbedaan hasil belajar yang signifikan antara siswa dengan motivasi tinggi dan rendah yang menggunakan startegi Graphic Organized What Happened dengan peserta didik yang diajar menggunakan strategi konvensional. Tidak ada interaksi yang signifikan antara strategi Graphic Organizer What Happened dan motivasi untuk keterampilan menulis narasi siswa. Kata kunci: Strategi Graphic Organizer What Happened, motivasi belajar, menulis narasi